Would You Rather Be Safe or Free? Motivational and Behavioral Aspects in COVID-19 Mitigation - Costantini, Giulio; Di Sarno, Marco; Preti, Emanuele; Richetin, Juliette; Perugini, Marco (Frontiers in Psychology, 2021)
This work investigates the relationship between goals and mitigation behaviors during the COVID-19 pandemic in Italy. Study 1 (pilot) identified goals ascribed to following and violating mitigation-related indications. Study 2 investigated the structure of and link between COVID-related goals and behaviors in a large community sample (N = 995, 301 men). Our results showed substantial relationships between goals and behaviors. Goals were best described by a bi-dimensional structure (being safe vs. being free), whereas behaviors clustered into a three-component structure (hygiene, distancing, going out). Hierarchical Multiple Regressions demonstrated the incremental validity of goals in the prediction of behaviors. Network Analysis suggested that goals imbued with social content were more directly related to both risky and preventive behaviors. Motivational aspects emerged as important contributors to the organization of behaviors in the context of the COVID-19 pandemic.